2015
DOI: 10.1016/j.jtcvs.2014.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Resection of thymoma should include nodal sampling

Abstract: Nodal status seems to be an important prognostic factor in patients with thymoma. Until the prognostic significance of nodal metastases is better understood, surgical therapy for thymoma should include sampling of regional lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
5
29
2
Order By: Relevance
“…However, studies from the United States have reported high lymphatic spread rate: 13.3% of 440 thymomas from the Surveillance, Epidemiology, and End Results program database. 8 The difference in metastatic rate might be due to differences in inclusion criteria. The study using the Surveillance, Epidemiology, and End Results database included only patients who had at least one lymph node analyzed pathologically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, studies from the United States have reported high lymphatic spread rate: 13.3% of 440 thymomas from the Surveillance, Epidemiology, and End Results program database. 8 The difference in metastatic rate might be due to differences in inclusion criteria. The study using the Surveillance, Epidemiology, and End Results database included only patients who had at least one lymph node analyzed pathologically.…”
Section: Discussionmentioning
confidence: 99%
“…The study using the Surveillance, Epidemiology, and End Results database included only patients who had at least one lymph node analyzed pathologically. 8 This might have included patients who underwent LND. Our data also clearly showed that LND increased the lymph node metastasis rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has certainly been the experience of the senior author of this review. More recent data from the SEER database (20) have shown, however, that as much as 15% of patients may have lymph node involvement and that all patients undergoing thymectomy for TETs should have routine sampling or even dissection of lymph nodes, especially of the nodes located in the anterior mediastinum (17,20).…”
Section: Controversies In Surgical Managementmentioning
confidence: 99%